2010
DOI: 10.3928/00989134-20100108-04
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the Threshold of Cancer and Aging: Integrating Gerontological and Oncological Nursing Knowledge and Skills

Abstract: Many tools are available for the assessment of pain in nonverbal older adults; however, guidelines are needed to help clinicians select the proper instrument for use in the nursing home setting. This article describes a project to identify clinically useful pain-behavioral assessment tools that have undergone sufficient psychometric testing. Phase 1 of the project included a comprehensive review and critique of currently available tools. In Phase 2 the National Nursing Home Pain Collaborative developed criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 61 publications
1
73
0
3
Order By: Relevance
“…During step 1, each tool was rated independently by 2 members of the working group with direct clinical experience (Ms Fay, Ms Gresley-Jones, Mr Joachimides, Dr Mankad, Dr Slonim) using criterion adapted from existing rating schemas developed to assess pain tools (Table 1). 42,43 Select content was modified and included 3 sections: usability (ie, format, length, scoring, suitable for population; Q1-4), comprehensiveness (ie, impact of pain, consideration of varied gross motor abilities, appropriate window; Q5-8) and other considerations (ie, additional measures, considerations of varied verbal abilities; Q9-10). 42,43 Working group members were asked to select a rating of clinical utility for each tool based upon the overall score (ie, weak, 0-5 points; moderate, 6-11 points; strong, 12-16 points) and strengths within usability, comprehensiveness, and other considerations.…”
Section: Clinical Utilitymentioning
confidence: 99%
“…During step 1, each tool was rated independently by 2 members of the working group with direct clinical experience (Ms Fay, Ms Gresley-Jones, Mr Joachimides, Dr Mankad, Dr Slonim) using criterion adapted from existing rating schemas developed to assess pain tools (Table 1). 42,43 Select content was modified and included 3 sections: usability (ie, format, length, scoring, suitable for population; Q1-4), comprehensiveness (ie, impact of pain, consideration of varied gross motor abilities, appropriate window; Q5-8) and other considerations (ie, additional measures, considerations of varied verbal abilities; Q9-10). 42,43 Working group members were asked to select a rating of clinical utility for each tool based upon the overall score (ie, weak, 0-5 points; moderate, 6-11 points; strong, 12-16 points) and strengths within usability, comprehensiveness, and other considerations.…”
Section: Clinical Utilitymentioning
confidence: 99%
“…The authors concluded that three scales: i) the Pain Assessment Checklist for Seniors with Limited Ability to Communicate (PACSLAC) (Fuchs-Lacelle & Hadjistavropoulos, 2004), ii) the Pain Assessment in Advanced Dementia (PAINAD) (Warden, Hurley, & Volicer, 2003), and iii) the DOLOPLUS-II (Wary, Serbouti, & Doloplus, 2001) were particularly commendable. Another expert consensus showed that the PACSLAC and the PAINAD were among the most relevant tools, considering their metrological qualities (Herr, Bursch, Ersek, Miller, & Swafford, 2010). Although these reviews do not allow to identify the ideal pain assessment tool (Kaasalainen, AkhtarDanesh, Hadjistavropoulos, Zwakhalen, & Verreault, 2013), accumulating data suggest that the PACSLAC could be an excellent choice for the health care professionals working 6 in a nursing home context Herr, Bursch, Ersek, Miller, & Swafford, 2010;Zwakhalen, Hamers, Abu-Saad, & Berger, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Another expert consensus showed that the PACSLAC and the PAINAD were among the most relevant tools, considering their metrological qualities (Herr, Bursch, Ersek, Miller, & Swafford, 2010). Although these reviews do not allow to identify the ideal pain assessment tool (Kaasalainen, AkhtarDanesh, Hadjistavropoulos, Zwakhalen, & Verreault, 2013), accumulating data suggest that the PACSLAC could be an excellent choice for the health care professionals working 6 in a nursing home context Herr, Bursch, Ersek, Miller, & Swafford, 2010;Zwakhalen, Hamers, Abu-Saad, & Berger, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Two other reviews 81,85 did report and discuss psychometric data, but not in a form suitable for this meta-review. Their choice of reporting may suggest authors' methodological concerns for the comparability and presentation of the data in quantitative form, given the heterogeneity of the studies and their methods.…”
mentioning
confidence: 99%
“…One review 80 focused on the barriers to successful pain assessment, identifying non-use of assessment tools as one such barrier. Two reviews were updated by, or related to, a later review by the same authors (Rutledge et al 75 is an update of Rutledge and Donaldson 76 -both excluded; Herr et al 81 is related to Herr et al 82 -the last included in our study -and aimed at reviewing the methods of the previous study). Two reviews 83,84 were reviews of reviews, and they were very specific in their aims, namely to identify pain assessment tools for adults with cognitive impairment recommended for use by paramedics 83 and district nurses.…”
mentioning
confidence: 99%